1999
DOI: 10.1084/jem.190.10.1439
|View full text |Cite
|
Sign up to set email alerts
|

Instruction for Cytokine Expression in T Helper Lymphocytes in Relation to Proliferation and Cell Cycle Progression

Abstract: T helper (Th) lymphocytes, when reactivated, recall expression of those cytokines they had been instructed to express in earlier activations, even in the absence of specific cytokine-inducing factors. In cells that memorize their expression, the cytokine genes are modified by chromatin rearrangement and demethylation, suggesting that they have been somatically imprinted. Here we show, by using inhibitors blocking the cell cycle in various stages, that for the instruction of a Th cell to express interleukin (IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
119
1
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(138 citation statements)
references
References 65 publications
13
119
1
5
Order By: Relevance
“…Using deterministic and stochastic models, we find that cell division expedites cell differentiation by shortening the time to achieve significant gene demethylation and cytokine expression in naive helper T cells. This finding is strongly supported by earlier observations reporting a correlation between cell division and the production of cytokines IL4 and IFNg, 22,23,60,61 without requiring a 'counting mechanism' in cells tracing the number of cell divisions they have completed. Furthermore, the expression of cytokines Il17A, Il17F and IL21, which are all related to the novel Th17 phenotype, is similarly found to correlate with cell division.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Using deterministic and stochastic models, we find that cell division expedites cell differentiation by shortening the time to achieve significant gene demethylation and cytokine expression in naive helper T cells. This finding is strongly supported by earlier observations reporting a correlation between cell division and the production of cytokines IL4 and IFNg, 22,23,60,61 without requiring a 'counting mechanism' in cells tracing the number of cell divisions they have completed. Furthermore, the expression of cytokines Il17A, Il17F and IL21, which are all related to the novel Th17 phenotype, is similarly found to correlate with cell division.…”
Section: Discussionsupporting
confidence: 85%
“…62 Our result underlines the fact that although the mean number of divisions required for high cytokine expression may be 3 or 4, the lowest number of divisions required for cytokine expression could be lower, including no cell division at all. 22 Contrary to naive helper T cells, our model finds that memory cells upregulate cytokine expression outright, without requiring cell division, as has also been shown experimentally. 63,64 One of the principle mechanisms that our model describes is derepression of cytokine loci through demethylation of CpG islets.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Most importantly, we and others have shown that imprinting of cytokine genes in activated naive T cells but not in memory T cells requires progression through the S phase of the first cell division. This is suggesting that imprinting is indeed linked to epigenetic modification of DNA and would explain why cytokine gene expression is faster in secondary than in primary immune reactions 90. Essentially everything that we think we know about memory T lymphocytes has been analyzed on T cells obtained from murine secondary lymphoid organs, mostly spleen, or human blood.…”
Section: Circulating Memory T Lymphocytesmentioning
confidence: 99%
“…Requirements for DNA synthesis or cell division have been reported in some, but not all studies (3)(4)(5)(6)(7)(8)(9), and activation is proposed to enable cells to express cytokine genes instructed by polarizing environmental cytokines. Evidence supporting such a model includes the ease with which T cells expressing a fixed pattern of cytokines can be expanded in vitro using distinct types of exogenous cytokines and the phenotype of cells prepared from various cytokine, cytokine-receptor, and cytokine signal-transducing Stat knockout mice (1,2).…”
mentioning
confidence: 99%